From Likes to Lies: Investigating University Students’ Ability to Detect and Analyze Fake News on Social Media (Journal of Asian Development Studies, 2025)
This study investigates university students’ ability to detect and analyze fake news on social media, with a particular focus on the roles of media literacy, critical thinking skills, and social media usage frequency. Using a quantitative survey design, data were collected from 208 students enrolled at the University of Management and Technology (UMT) and the University of Sialkot (USKT). Descriptive statistics and multiple regression analysis were employed to examine the predictive relationship between the independent variables and students’ ability to identify fake news. The findings reveal that media literacy and critical thinking skills significantly enhance students’ ability to detect fake news, whereas excessive social media use negatively affects accurate identification. The study is grounded in Uses and Gratifications Theory, emphasizing students' active roles in media consumption and evaluation. The results highlight the importance of integrating media literacy and critical thinking education into higher education curricula to mitigate the spread and impact of misinformation in digital environments.